Astrocyte IP3R2-dependent Ca2+ signaling is not a major modulator of neuronal pathways governing behavior - Petravicz, Jeremy; Boyt, Kristen M.; McCarthy, Ken D. (Frontiers in Behavioral Neuroscience, 2014)
Calcium-dependent release of gliotransmitters by astrocytes is reported to play a critical role in synaptic transmission and be necessary for long-term potentiation (LTP), long-term depression (LTD) and other forms of synaptic modulation that are correlates of learning and memory . Further, physiological processes reported to be dependent on Ca2+ fluxes in astrocytes include functional hyperemia, sleep, and regulation of breathing. The preponderance of findings indicate that most, if not all, receptor dependent Ca2+ fluxes within astrocytes are due to release of Ca2+ through IP3 receptor/channels in the endoplasmic reticulum. Findings from several laboratories indicate that astrocytes only express IP3 receptor type 2 (IP3R2) and that a knockout of IP3R2 obliterates the GPCR-dependent astrocytic Ca2+ responses. Assuming that astrocytic Ca2+ fluxes play a critical role in synaptic physiology, it would be predicted that eliminating of astrocytic Ca2+ fluxes would lead to marked changes in behavioral tests. Here, we tested this hypothesis by conducting a broad series of behavioral tests that recruited multiple brain regions, on an IP3R2 conditional knockout mouse model. We present the novel finding that behavioral processes are unaffected by lack of astrocyte IP3R-mediated Ca2+ signals. IP3R2 cKO animals display no change in anxiety or depressive behaviors, and no alteration to motor and sensory function. Morris water maze testing, a behavioral correlate of learning and memory, was unaffected by lack of astrocyte IP3R2-mediated Ca2+-signaling. Therefore, in contrast to the prevailing literature, we find that neither receptor-driven astrocyte Ca2+ fluxes nor, by extension, gliotransmission is likely to be a major modulating force on the physiological processes underlying behavior.